Diberkati Untuk Menjadi Berkat Kajian Hermeneutik Atas Kitab Kejadian Pasal 12:1-9 - Mandagi, Lamberty Yahya (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
This paper is a hermeneutic work based on the book of Genesis chapter 12.1-9 and given a title : Blessed To Be A Blessing. This point is brought up for re-awekening to church members, that basically as believers in the LORD God in Jesus Christ, we are colling to be blessing for many people and not to bring a burden of suffering to others. Because there are many acts of violence and even murder involving Christians. In carring out hermeneutical work on Genesis chapter 12.1-9, the author uses a critical historical method. Through work on this text is can be concluded that God calls people to be blessed and to be a blessing to many people.